THE PREVALENCE AND PHENOMENOLOGY OF PSYCHOTIC SYMPTOMS IN DEMENTIA SUFFERERS - Ballard, C; Saad, K; Patel, A; Gahir, M; Solis, M; Coope, B; Wilcock, G (1995)
One hundred patients referred to old age psychiatry services in the West Midlands and 25 patients referred to a memory clinic in Bristol with mild to moderate dementia were assessed using the GMS/HAS schedule together with a detailed inventory to assess their psychotic symptoms. On careful evaluation one patient did not have dementia. Eighty-three of the other 124 patients (66.9%) had at least one psychotic symptom. The prevalence of psychotic symptoms in the patients from the West Midlands and from the memory clinic in Bristol were extremely similar. Thirty-five per cent had at least one visual hallucination, 12.9% had at least one auditory hallucination, 48.4% had at least one delusional belief and 29.0% had at least one delusional misperception. Most individuals experienced their psychotic symptoms at a frequency between weekly and daily. Twenty-four had no insight into their psychotic symptoms and acted upon them, while only one patient had full insight into their symptoms. Thirty-seven subjects were mildly distressed and 14 were severely distressed by the psychotic symptoms they experienced. There was a trend for patients with cortical Lewy body dementia to be more likely to have psychotic symptoms than patients with Alzheimer's disease or vascular dementia. The symptom profile of psychotic symptoms in the different dementias was, however, very similar. The frequencies of individual psychotic symptoms are described in the text.